The Influence of Locus of Control, Study Habits and Gender on the Academic Achievement of Senior Secondary School Physics Students in Ibadan Metropolis - Uchenna Okeke; Edidiong Ukoh (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2020)
The study investigated the relationship between Locus of Control, Study Habit, Gender and Academic Achievement of senior secondary school physics students in Ibadan metropolis. The descriptive survey research design was adopted. Seven hundred and fifty senior secondary two (SS2) Physics students were randomly selected from 30 schools in the five local Governments areas of Ibadan Metropolis. Three instruments were used for data collection. The instruments are Physics Achievement Test (PAT) (r = 0.70), Locus of Control Scale (LOCS) (0.86) and Study Habit Questionnaire (SHQ) (0.89). Two (2) research questions were answered, using inferential statistics of t-test, and multiple regression analysis. Findings of the study showed that there is a relationship between locus of control and Academic Achievement [r=0.216, n=750,p= <0.01]. It was found that Locus of Control, Study Habits and Gender predicted students' academic achievement of Students, with R=0.203, which is equivalent to 20.3%. This however indicates a poor level of prediction. R2 = 0.041, which is equivalent to 4.1%, indicating a very poor level of shared variance between the dependent variable and the independent variables. The study recommends the adoption of the instructional methods that will enhance students' locus of control and the promotion of good study habits among senior secondary school physics students. Governments, education administrators, and school authorities should consider the joint interactive influence of locus of control, study habits and gender when designing programs for physics.